2015
DOI: 10.1016/j.celrep.2015.09.069
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Role of IL-21-Induced BATF in Sustaining CD8-T-Cell-Mediated Chronic Viral Control

Abstract: Summary Control of chronic viral infections by CD8 T cells is critically dependent on CD4 help. In particular, helper-derived IL-21 plays a key role in sustaining the CD8 T cell response, however the molecular pathways by which IL-21 sustains CD8 T cell immunity remain unclear. We demonstrate that IL-21 causes a phenotypic switch of transcription factor expression in CD8 T cells during chronic viral infection characterized by sustained BATF expression. Importantly, BATF expression during chronic infection is b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
92
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(99 citation statements)
references
References 40 publications
4
92
0
Order By: Relevance
“…Our findings revealed that BATF transcript is upregulated in tumor-infiltrating Treg cells more than in tumor infiltrating Th17 cells (Figure S4). Expression of BATF in CD8 + T cells is induced by IL-21 (Xin et al., 2015), and we found that IL21R is highly expressed in tumor-infiltrating Treg cells (Figure 4). …”
Section: Discussionmentioning
confidence: 99%
“…Our findings revealed that BATF transcript is upregulated in tumor-infiltrating Treg cells more than in tumor infiltrating Th17 cells (Figure S4). Expression of BATF in CD8 + T cells is induced by IL-21 (Xin et al., 2015), and we found that IL21R is highly expressed in tumor-infiltrating Treg cells (Figure 4). …”
Section: Discussionmentioning
confidence: 99%
“…For example, several promising molecules that we identified, such as CD38, CD39, BATF, NAB1, KIR2DL4, SIPRG and components of Notch signaling, deserve further investigation as immunotherapeutic targets in cancer. BATF has been shown to regulate the metabolism and survival of CD8 + T cells and to diminish the inhibited phenotype of CD8 + T cells 48,49 . In a model of infection with lymphocytic choriomeningitis virus, the expression of BATF in CD8 + T cells, induced by the cytokine IL-21 derived from CD4 + T cells, was shown to be essential for maintaining the effector response of CTLs, and overexpression of BATF restored the effector function of CD8 + T cells that had not received help from CD4 + T cells 49 .…”
Section: Discussionmentioning
confidence: 99%
“…BATF has been shown to regulate the metabolism and survival of CD8 + T cells and to diminish the inhibited phenotype of CD8 + T cells 48,49 . In a model of infection with lymphocytic choriomeningitis virus, the expression of BATF in CD8 + T cells, induced by the cytokine IL-21 derived from CD4 + T cells, was shown to be essential for maintaining the effector response of CTLs, and overexpression of BATF restored the effector function of CD8 + T cells that had not received help from CD4 + T cells 49 . NAB1 is a transcription factor whose mouse homolog (NAB2) is induced in CD8 + T cells that have received help from CD4 + T cells and is needed to prevent activation-induced cell death of those ‘helped’ CD8 + T cells 50 .…”
Section: Discussionmentioning
confidence: 99%
“…revealed that IL-21 maintains functional CD8 T cells during chronic LCMV infection by sustaining the expression of the transcription factor basic leucine transcription factor, ATF-like (BATF) via the activation of STAT3 [76]. In vitro studies further indicate that IL-21-induced BATF cooperates with IRF4 to induce the expression of the transcriptional regulator B lymphocyte-induced maturation protein 1 (Blimp1) [76], which can both enhance the effector functions of CD8 T cells [7779], as well as exacerbate exhaustion and the expression of inhibitory receptors [78]. Indeed, BATF-deficient virus-specific CD8 T cells express lower levels of the inhibitory receptors PD-1 and 2B4 [76].…”
Section: Il-21 and Cd8 T Cell Differentiation And Maintenancementioning
confidence: 99%
“…In vitro studies further indicate that IL-21-induced BATF cooperates with IRF4 to induce the expression of the transcriptional regulator B lymphocyte-induced maturation protein 1 (Blimp1) [76], which can both enhance the effector functions of CD8 T cells [7779], as well as exacerbate exhaustion and the expression of inhibitory receptors [78]. Indeed, BATF-deficient virus-specific CD8 T cells express lower levels of the inhibitory receptors PD-1 and 2B4 [76]. Therefore, it will be important to pinpoint how the IL-21-STAT3-BATF axis controls the levels of Blimp1 and how its regulatory activities are influenced by the degree of antigenic stimulation and presence of other activating or inhibitory signals.…”
Section: Il-21 and Cd8 T Cell Differentiation And Maintenancementioning
confidence: 99%